Insight into sludge dewatering by advanced oxidation using persulfate as oxidant and Fe2+ as activator: Performance, mechanism and extracellular polymers and heavy metals behaviors. (15th June 2021) - Guo, Junyuan; Gao, Qifan; Chen, Yihua; He, Qianlan; Zhou, Hengbing; Liu, Jinbao; Zou, Changwu; Chen, Wenjing
Abstract: This study established a Fe 2+ /persulfate oxidation system to dewater sludge in WWTPs. Dewatering performance, persulfate consumption and the variations of sludge pH, TN and TP during dewatering process were monitored. EPS and ζ-potential behaviors for ameliorating sludge dewatering was investigated. Transformation, leaching toxicity and environmental risk of heavy metals in sludge during dewatering were determined. Results demonstrated that after treated by Fe 2+ /persulfate oxidation system with 0.6 mmol/g–VS of persulfate at Fe 2+ /persulfate molar ratio 0.6, WC decreased to 53.5% and SCST increased to 4.15, which implied an excellent improvement of sludge dewatering. The fast persulfate consumption, the decrease of sludge pH and the increase of TN illustrated the positive effects of Fe 2+ in activating persulfate and the decomposition of EPS by the activation products, SO4 − and OH. Another product (Fe 3+ ) generated during persulfate activation could decrease the content of phosphorus-containing matter (released from EPS decomposition) through the precipitation reaction with PO4 3− . The decrease of TOC and UV–254 happened in HPO–A, HPO–N and TPI–A organic substance of EPS (mainly contained in TB–EPS fraction) indicated that the destruction of hydrophobic organic matter of EPS would stimulate the release of bound water, which was beneficial to dewater sludge. The largest protein loss in TB–EPS (from 24.5 to 10.7 mg/L) indicated that the effective decomposition of TB–EPS could significantly ameliorate sludge dewatering. The increase of ζ–potential indicated the degradation of organic matter in EPS with negative charge. To sum up, the destruction of protein–like substances in hydrophobic organic matter of TB–EPS was the main mechanism for improving sludge dewatering by Fe 2+ /persulfate oxidation system. 3D–EEM fluorescence spectroscopy analysis proved that these protein–like substances were mainly tryptophan protein and humic acid. Moreover, due to the disruption of EPS, the contents of heavy metals in sludge, and their leaching toxicity and environmental risk were reduced. Therefore, Fe 2+ /persulfate oxidation system has potential and application prospects to improve sludge dewatering and optimize sludge management in WWTPs. Graphical abstract: Image 1 Highlights: Fe 2+ –activated persulfate helped break down extracellular polymers in sludge. Decomposition of extracellular polymers in sludge facilitated sludge dewatering. Breakage of hydrophobic organics in extracellular polymers promoted sludge dewatering. Protein in extracellular polymers adversely affected on sludge dewatering.